Pengaruh Brand Image, Electronic Word Of Mouth dan Promosi terhadap Keputusan Pembelian : (Studi pada Pengguna Tiktok Shop di Jakarta Selatan) - Falah Khairunnisa; Yugi Setyarko (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2025)
This study aims to determine the effect of brand image, electronic word of mouth, and promotions on purchasing decisions. The data source used in this research is primary data collected through the distribution of questionnaires. The population of this study consists of TikTok Shop users in South Jakarta. The sampling technique used is nonprobability sampling, with a purposive sampling method based on Lemeshow's formula, resulting in a sample size of 98 respondents. The analytical tool used is SPSS version 29. The findings of this study indicate that brand image, electronic word of mouth, and promotions have a significant effect on Purchasing Decisions.